2022
DOI: 10.1021/acsnano.2c06504
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Growth of Gold Nanoparticles in the Low-Temperature Water–Gas Shift Reaction

Abstract: Supported gold nanoparticles are widely studied catalysts and are among the most active known for the low-temperature water–gas shift reaction, which is essential in fuel and energy applications, but their practical application has been limited by their poor thermal stability. The catalysts deactivate on-stream via the growth of small Au nanoparticles. Using operando X-ray absorption and in situ scanning transmission electron microscopy, we report direct evidence that this process can be reversed by carrying o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…A fast and wide range of water partial pressure switch (0–100% relative humidity) and the independent control of gas parameters like pressure, flow rate, gas composition, and the level of water vapor are therefore achievable. By using the vaporization component, Hutchings et al directly observed the growth of supported Au nanoparticles under water–gas shift reaction conditions by in situ TEM, and this on-stream deactivated Au catalysts could be reactivated via a facile oxidative treatment, which redisperses the Au nanoparticles. In addition, the surface reconstruction of commercial Cu/ZnO/Al 2 O 3 catalysts induced by the CH 3 OH steam is also investigated using the windowed gas cell approach and in situ STEM analysis .…”
Section: In Situ Electron Microscopymentioning
confidence: 99%
“…A fast and wide range of water partial pressure switch (0–100% relative humidity) and the independent control of gas parameters like pressure, flow rate, gas composition, and the level of water vapor are therefore achievable. By using the vaporization component, Hutchings et al directly observed the growth of supported Au nanoparticles under water–gas shift reaction conditions by in situ TEM, and this on-stream deactivated Au catalysts could be reactivated via a facile oxidative treatment, which redisperses the Au nanoparticles. In addition, the surface reconstruction of commercial Cu/ZnO/Al 2 O 3 catalysts induced by the CH 3 OH steam is also investigated using the windowed gas cell approach and in situ STEM analysis .…”
Section: In Situ Electron Microscopymentioning
confidence: 99%
“…The real-time X-ray absorption spectroscopy (XAS) method showed the formation of monatomic gold centers from nanoparticles, which are highly active in the reaction of obtaining vinyl chloride. Additionally, Hutchings and co-workers, using in situ HAADF-STEM and XAS, showed that in the water–gas shift reaction (WGS, CO + H 2 O ⇌ CO 2 + H 2 ), enlargement of Au particles deactivated the catalyst, whereas oxidative treatment dispersed the nanoparticles into smaller particles and restored catalytic activity. The catalytic reaction of CO oxidation was also studied on the Au–Ag bimetallic alloy by the ETEM method . The nanoparticles behave dynamically; the introduction of O 2 or CO molecules leads to a visual change in the catalyst nanofaces, and the metal atoms rearrange along the {110} faces (Figure H).…”
Section: Analysis Of the Dynamic Behavior And Variability Of Catalyti...mentioning
confidence: 99%
“…Gold nanoparticles (GNPs), particularly those with chiral structures, have become popular in recent decades because of their excellent catalytic activities, optoelectronic properties, and biological activities. , The use of soft templates is a common and effective method for obtaining GNPs with precise sizes and specially assembled shapes. , Recently, hydrogels formed by LMWGs have been widely used as soft templates for in situ preparing GNPs. Abundant aggregate structures in supramolecular hydrogels are expected to effectively produce GNPs with diverse morphologies.…”
Section: Introductionmentioning
confidence: 99%